2020
DOI: 10.1111/ahe.12548
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐off expression of melatonin receptor subtypes (Mel1a and Mel1b) and androgen receptor in lung of a tropical bird, Perdicula asiatica

Abstract: The role of circulatory steroid hormone along with melatonin in lung of any seasonally breeding bird has never been explored so far. This could be interesting because steroid hormones are immunosuppressive while melatonin is immunostimulatory in nature. In our present study, we report the effect of exogenous melatonin and testosterone on expression of melatonin receptor subtypes (Mel1a and Mel1b) and androgen receptor in lung of a tropical bird Perdicula asiatica. Birds were collected from vicinity of Varanasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Therefore, we treated cauda epididymal epithelial cells cultured in vitro with DHT and observed that DHT inhibited MEL secretion and receptor expression in epididymal epithelial cells. Exogenous T has been reported to modulate AR expression and down‐regulate the expression of MEL receptors (Kharwar et al, 2020), whereas MEL secretion increases in patients with gonadotropin deficiency and decreases in patients with hypo‐testosterone and high gonadotropin hypogonadism, suggesting that both gonadotropin and gonadal steroid hormones regulate MEL secretion in human blood (Luboshitzky et al, 1996). DHT, a more potent steroid hormone than T (Marchetti & Barth, 2013; Saartok et al, 1984; Wright et al, 1999), can participate in the physiological regulation of the epididymis by regulating MEL secretion and receptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we treated cauda epididymal epithelial cells cultured in vitro with DHT and observed that DHT inhibited MEL secretion and receptor expression in epididymal epithelial cells. Exogenous T has been reported to modulate AR expression and down‐regulate the expression of MEL receptors (Kharwar et al, 2020), whereas MEL secretion increases in patients with gonadotropin deficiency and decreases in patients with hypo‐testosterone and high gonadotropin hypogonadism, suggesting that both gonadotropin and gonadal steroid hormones regulate MEL secretion in human blood (Luboshitzky et al, 1996). DHT, a more potent steroid hormone than T (Marchetti & Barth, 2013; Saartok et al, 1984; Wright et al, 1999), can participate in the physiological regulation of the epididymis by regulating MEL secretion and receptor expression.…”
Section: Discussionmentioning
confidence: 99%